2014
DOI: 10.3892/etm.2014.1592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-tocotrienol in counteracting oxidative stress and joint damage in collagen-induced arthritis in rats

Abstract: Tocotrienols exhibit a significant anti-inflammatory and antioxidant effect in numerous human diseases. However, the anti-inflammatory and antioxidant effects of tocotrienols in arthritic conditions are not well documented. Therefore, the effect of γ-tocotrienol supplementation against oxidative stress and joint pathology in collagen-induced arthritis in rats was investigated in the present study. Adult female Dark Agouti rats were randomly divided into groups: Control, γ-tocotrienol alone, arthritis alone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 38 publications
3
35
0
3
Order By: Relevance
“…Although, Radhakrishnan et al [26] reported no significant deviation in body weight between the TT-treated and control groups, the difference in observations may be due to divergence in the dose of TT used. Radhakrishnan et al [26] have used 5 mg of γTT/Kg body weight for 24 d, while 10 mg of TT is orally fed to each rat each day for 14 d in the current experiment. Interestingly, the groups of rats did not differ in terms of food intake, while the TT+group has consumed the noticeably higher amount of water starting from post-TT treatment.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although, Radhakrishnan et al [26] reported no significant deviation in body weight between the TT-treated and control groups, the difference in observations may be due to divergence in the dose of TT used. Radhakrishnan et al [26] have used 5 mg of γTT/Kg body weight for 24 d, while 10 mg of TT is orally fed to each rat each day for 14 d in the current experiment. Interestingly, the groups of rats did not differ in terms of food intake, while the TT+group has consumed the noticeably higher amount of water starting from post-TT treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Radhakrishnan et al [26] also have reported insignificant alterations in the serum SOD activity after 24 d of oral supplementation γTT (5 mg/Kg). No alteration in activities of serum catalase, SOD, GPx and GR has been noticed in any of the tested time points during the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete antioxidant defense system is well-evolved, and includes antioxidant enzymes, antioxidants and a variety of other mechanisms tasked with damage repair and re-synthesis (4). The coordination and complementation of the various antioxidant defense systems in vivo guarantee their stable and effective involvement in the antioxidative stress effect.…”
Section: Introductionmentioning
confidence: 99%
“…ROS such as •OH, superoxide anions, hydrogen peroxide and hypochlorous acid are reportedly formed in the inflamed joints of patients with RA by nicotinamide adenine dinucleotide phosphate oxidase, xanthine oxidase and cytochrome P450 monooxygenase, as well as mitochondrial respiratory chain dysfunction, in chondrocytes, activated macrophages and neutrophils [15][16][17]. Moreover, antioxidant therapy ameliorated arthritis in animal models; for example, α-tocotrienol exhibited significant antioxidant and anti-inflammatory effects on collagen-induced arthritis in rats,34 and the transfection of extracellular superoxide dismutase and catalase genes ameliorated antigen-induced arthritis in rats 35. H 2 quenches only harmful ROS, such as •OH and ONOO − , and it can permeate cell membranes and easily target organelles, including mitochondria and nuclei 18.…”
mentioning
confidence: 99%